Integration of the National Curriculum and the Pesantren Curriculum at Madrasah Aliyah Keagamaan Hamzanwadi II Nahdlatul Wathan: A Managerial Analysis - Siti Rahmah Hayati; Yudin Citriadin; Nurul Yakin; Subki Subki (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study examines the managerial strategies employed in integrating the National Curriculum and the Pesantren Curriculum at MA Keagamaan Hamzanwadi II Nahdlatul Wathan. The madrasah has demonstrated significant quality improvement, reflected in its accreditation B status, and implements a boarding school system aimed at producing graduates proficient in Qur’anic literacy, Hadith memorisation, classical Islamic texts, and bilingual language skills, alongside strong character development. Using a qualitative descriptive approach based on secondary data and literature review, the study finds that the curriculum integration is effectively managed through strategic planning, stakeholder collaboration, and the alignment of academic and religious objectives. Extracurricular activities complement the formal curriculum to support holistic student development. The madrasah’s vision and mission emphasise faith, knowledge, moral integrity, and patriotism, which are realised through adaptive leadership and an immersive educational environment. This integrative management model offers a valuable example for Islamic educational institutions striving to balance national academic standards with pesantren traditions